Analisis Pelaksanaan Penyidikan Tindak Pidana Kekerasan dan Pengeroyokan di Wilayah Hukum Kepolisian Sektor Pangkalan Balai Kabupaten Banyuasin - Muryanto, Febri; Novaria, Eva; Sutinah, Sutinah (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2023)
This study aims to analyze the implementation of investigations into criminal acts of violence and assault in the jurisdiction of the National Police Headquarters, Banyuasin Regency. The method used is a qualitative descriptive analysis technique. The results of the investigation show that the investigation into criminal acts of violence and assault in the jurisdiction of the Banyuasin Police has been going well. This can be seen in the Jurisdiction of the Basic Fields of the Banyuasin Police, based on an analysis of the implementation of investigations into crimes of violence and assault, which includes the steps and indicators used, namely: planning (officers; resources/budget; infrastructure) ) implementation (objectives; division of tasks and responsibilities) answer); implementation (research activities; communication related to coordination); Supervision and control; Data collection and reporting, all carried out properly. The need for optimizing the handling of violent and attempted crimes by perpetrators of crime, especially criminal acts of minors, or increasing the attention of the police apparatus in handling criminal acts or handling criminal acts committed by children against their peers; Take more effective preventive, deterrent and repressive measures to deal with criminal violence and abuse, as they often involve minors.